PENGARUH BUDAYA KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN KAPUAS - Artom Ali; Akhmad Abdurahman (STIA Bina Banua Banjarmasin, 2021)
Abstract: This study aims to determine and analyze the effect of: (1) work culture and (2) organizational climate on the performance of the employees of the Kapuas Regency Ministry of Religion. The type of research used is the explanatory method. The population to be studied includes all employees of the Kapuas Regency Ministry of Religion, totaling 57 people. The sampling technique used